Emotional intelligence in team sports : relationship of role ambiguity and intra-team communication with pre-performance psychobiosocial states - Nateri, Rachele (2018)
The aim of the present study was to explore the relationships between athletes’ emotional intelligence (EI), group processes and feeling states in the context of team sports. Italian athletes (N=299) completed a self-report multi-section questionnaire to measure: emotional intelligence (TEIQue-SF; Cooper and Petrides, 2010), intra-team communication efficacy (SECTS; Sullivan and Short, 2011), role ambiguity (RAS; Beauchamp, Bray, Eys and Carron, 2002) and psychobiosocial states (PBS-ST; Robazza, Bertollo, Ruiz and Bortoli, 2016). As expected, multiple regression analysis and path analysis results showed a significant and positive relationship between emotional intelligence and functional psychobiosocial states and positive aspects of communication efficacy (i.e., positive conflict and acceptance). A significant negative relationship was found between emotional intelligence, role ambiguity, and dysfunctional psychobiosocial states. EI predicts functional states, whether acceptance and positive conflict have a role of mediators between these two variables. Furthermore, EI, as hypothesized, was negative related to dysfunctional psychobiosocial states and role ambiguity. Hence, a low level of EI predicts dysfunctional states whether role ambiguity behave as mediator. It is suggested that future research should focus also on the role of the coach, investigating coach’s emotional intelligence and its influence on both athlete’s emotion regulation and pre-performance psychobiosocial states.